Article 2. Structural position of suites and strata of the “Bug series” - Kyrylyuk, V.P. (Geofizicheskiy Zhurnal, 2023)
The name “Bug Series” was introduced into the Precambrian stratigraphic scheme of the Ukrainian Shield more than half a century ago. During this period, ideas about the composition and age of the series changed several times, but at the same time, until recently, the opinion of various studies about its stratigenic nature remained unchanged. In recent years, a number of publications have appeared in which other views on the origin of the “Bug series” are expressed. Initially, they concerned only individual petrographic groups, such as carbonate and magnetite-bearing rocks, which were attributed to endogenous (magmatic) origin. Later, an opinion was expressed about the nonstratigenic origin of the entire “Bug Series”, and some authors propose to abandon the dismemberment of the Early Precambrian granulite complexes into suites altogether. These ideas are based only on the materials of the study of local objects obtained by drilling and geophysical methods, and they do not take into account the results of regional geological and stratigraphic studies. Simultaneously with new ideas about the genesis of the “Bug series”, an attempt is being made to link its origin with faults and to revise its age. In order to discuss the problem of the “Bug series”, a series of publications has been prepared, presenting the main generalizations of many years of regional geological and thematic studies on the composition, structure, stratigraphic and structural position of the units belonging to the “Bug series”. The cycle consists of three separate articles. The first article characterizes the composition of subdivisions and rock associations included in the “Bug series” in the current Precambrian stratigraphic scheme of the Ukrainian Shield. In this second article of the cycle, ideas about the structural position of the “Bug series” and its subdivisions are considered. For a long time there was an opinion that the “Bug series” performed synclines “superimposed” on the ancient foundation. These ideas we-re convincingly refuted more than half a century ago on the example of the stratotype section of the Bug series in the area of Zavallia [Vinogradov, 1970], but sometimes some researchers still adhere to them. The data presented in this article indicate that all units that now belong to the “Bug series” are suites and strata that are part of a single Bug Area granulite complex and occupy a clearly defined stratigraphic and structural position in its section. Ideas about the connection of the “Bug series” with “superimposed” synclines or faults do not have any reliable justification.